E-MONEY PAYMENT TRANSACTIONS FOR M1 MONEY REQUESTS BEFORE AND AFTER THE COVID-19 PANDEMIC - Rismawati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This article has two objectives, to prove that E-Money payment transactions with an indicator of the value of E-Money transactions can affect the demand for M1 money, and to see the effect before and after the Covid-19 pandemic using a dummy variable. This article was written using monthly time series research data and using the VECM method. The results of the analysis show that the short-term estimation results have two NEM variables in the 1st lag, and the 2nd lag has a positive effect on the five percent significance level. As for the long-term estimation results, there are no significant variables. In addition, in the period before the Covid-19 pandemic and during the Covid-19 Pandemic, it was seen that there was a decrease in the amount of E-Money given to M1 Money Requests when compared to the period before the Covid-19 pandemic. Meanwhile, the results of the study on the Covid-19 pandemic dummy variable showed an impact on the decline in money demand.